Peningkatan Kompetensi CAD 3D Siswa SMK Negeri 5 Surabaya Melalui Pelatihan Autodesk Inventor Berbasis Project-Based Learning - Widya Emilia Primaningtyas; Fais Hamzah; Sindi Wahyu Pratiwi; Ludia Ni'matuzzahroh; Muhammad Rizqi Khoironi Fadhli; Nadiyatul Fitriyah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Vocational High Schools (SMK) have a strategic function in preparing graduates who are in line with the demands of the industrial world. However, approximately 55% of SMK graduates in Indonesia still do not achieve the expected competency standards, especially in the fields of digital technology-based engineering and manufacturing. One factor contributing to this condition is the limited mastery of 3D Computer-Aided Design (CAD) software, especially Autodesk Inventor. This activity is designed to improve the ability of SMK students in operating Autodesk Inventor through an intensive training program organized by the Design and Manufacturing Engineering Study Program of the Surabaya State Polytechnic of Shipping (PPNS) for students of SMK Negeri 5 Surabaya. The training program was attended by 85 students and was implemented using a participatory approach and Project-Based Learning. Assessment of learning outcomes was carried out through a comparison of pre-test and post-test scores analyzed using the Wilcoxon Signed-Rank test. The results of the analysis showed a significant increase in students' abilities in using Autodesk Inventor, as reflected in the difference in scores before and after the training. In general, this activity contributes positively to strengthening the technical skills of vocational school students while strengthening collaboration between universities and vocational schools in developing industrial technology-based competencies.ABSTRAKSekolah Menengah Kejuruan (SMK) memiliki fungsi strategis dalam menyiapkan lulusan yang selaras dengan tuntutan dunia industri. Akan tetapi, sekitar 55% lulusan SMK di Indonesia masih belum mencapai standar kompetensi yang diharapkan, terutama pada bidang teknik dan manufaktur berbasis teknologi digital. Salah satu faktor yang berkontribusi terhadap kondisi tersebut adalah keterbatasan penguasaan software Computer-Aided Design (CAD) 3D, khususnya Autodesk Inventor. Kegiatan ini dirancang untuk meningkatkan kemampuan siswa SMK dalam mengoperasikan Autodesk Inventor melalui program pelatihan intensif yang diselenggarakan oleh Program Studi Teknik Desain dan Manufaktur Politeknik Perkapalan Negeri Surabaya (PPNS) bagi siswa SMK Negeri 5 Surabaya. Program pelatihan diikuti oleh 85 siswa dan dilaksanakan dengan menerapkan pendekatan partisipatif serta Project-Based Learning. Penilaian capaian pembelajaran dilakukan melalui perbandingan skor pre-test dan post-test yang dianalisis menggunakan uji Wilcoxon Signed-Rank. Hasil analisis menunjukkan adanya peningkatan kemampuan siswa secara signifikan dalam penggunaan Autodesk Inventor, yang tercermin dari perbedaan skor sebelum dan sesudah pelatihan. Secara umum, kegiatan ini berkontribusi positif terhadap penguatan keterampilan teknis siswa SMK sekaligus mempererat kolaborasi antara perguruan tinggi dan sekolah kejuruan dalam pengembangan kompetensi berbasis teknologi industri.